Organic farming offers promising mitigation potential in dairy systems without compromising economic performances. (15th May 2023) - Lambotte, Mathieu; De Cara, Stéphane; Brocas, Catherine; Bellassen, Valentin
Abstract: There is a lack of clear empirical evidence towards the lower carbon footprint of organic food products, in particular in the dairy sector. Until now, small sample sizes, lack of properly defined counterfactual and the omission of land-use related emissions have hindered comparisons of organic and conventional products. Here we bridge these gaps by mobilizing a uniquely large dataset of 3074 French dairy farms. Using propensity score weighting, we find that the carbon footprint of organic milk is 19% (95% CI = [10%–28%]) lower than its conventional counterpart without indirect land-use change and 11% (95% CI = [5%–17%]) lower with indirect land use changes. In both production systems, farms' profitability is similar. We simulate the consequences of the Green deal target of 25% of agricultural land devoted to organic dairy farming and show that this policy would reduce the greenhouse gas emissions of the French dairy sector by 9.01–9.64%. Highlights: Carbon footprint of organic milk is 19% lower than its conventional counterpart. When indirect land-use changes are included, the difference shrinks to 11%. Organic and conventional farms have similar economic performances. Reaching 25% of organic milk in France would reduce GHGE of the dairy sector by 9%. Controlling for structural differences is essential in environmental evaluations.